2013
DOI: 10.1371/journal.pone.0080647
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of a New Composite Mesh for the Repair of Full-Thickness Abdominal Wall Defects in a Rabbit Model

Abstract: IntroductionComposite biomaterials designed for the repair of abdominal wall defects are composed of a mesh component and a laminar barrier in contact with the visceral peritoneum. This study assesses the behaviour of a new composite mesh by comparing it with two latest-generation composites currently used in clinical practice.MethodsDefects (7x5cm) created in the anterior abdominal wall of New Zealand White rabbits were repaired using a polypropylene mesh and the composites: PhysiomeshTM; VentralightTM and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Searching the PubMed database, we found only few experimental and comparative studies, which were mainly in animal models. Most of the articles show similar results in terms of mechanical properties, adhesion characteristics and histological testing [27][28][29]. The main disadvantage of those studies was the short observation time periods after the mesh implementations, which went from the 14th to the 28th day.…”
Section: Discussionmentioning
confidence: 81%
“…Searching the PubMed database, we found only few experimental and comparative studies, which were mainly in animal models. Most of the articles show similar results in terms of mechanical properties, adhesion characteristics and histological testing [27][28][29]. The main disadvantage of those studies was the short observation time periods after the mesh implementations, which went from the 14th to the 28th day.…”
Section: Discussionmentioning
confidence: 81%
“…Their architecture is perfectly adapted for intraperitoneal placement as the anti-adhesive barrier side prevents postoperative attachment of visceral tissues and the mesh is appropriate for tissue integration in the abdominal wall. In a previous preclinical study [17], we used sequential laparoscopy to evaluate the ability of three distinct composite meshes that differ by architecture and chemical composition to prevent the formation of postoperative adhesions. All composites displayed adequate peritoneal behavior with minimal adhesion formation.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study performed by our group [17], we analyzed the behavior of various composite meshes at the peritoneal interface as well as their tissue integration. In that study, the seroma and FBR observed with some of the implants caught our attention.…”
Section: Introductionmentioning
confidence: 99%
“…In general terms, a hernia is classified as the protrusion of organs through an opening in the cavity that is intended to contain them [5]. The most common hernias are inguinal, ventral, incisional, femoral, umbilical, hiatal, and epigastric [6].…”
Section: Introductionmentioning
confidence: 99%